L'identité africaine dans « L’appel des arènes » et « Le vent du sud » - Dr Johnson Djoa Manda (Annales du Patrimoine, 2016)
Dr Johnson Djoa Manda, L'identité africaine dans « L’appel des arènes » et « Le vent du sud »